Monitoring the in vivo siRNA release from lipid nanoparticles based on the fluorescence resonance energy transfer principle - Sun, Lei; Zhang, Jinfang; Zhou, Jing-e; Wang, Jing; Wang, Zhehao; Luo, Shenggen; Wang, Yeying; Zhu, Shulei; Yang, Fan; Tang, Jie; Lu, Wei; Wang, Yiting; et al. (Asian journal of pharmceutical sciences, 2023)
The siRNA-loaded lipid nanoparticles have attracted much attention due to its significant gene silencing effect and successful marketization. However, the in vivo distribution and release of siRNA still cannot be effectively monitored. In this study, based on the fluorescence resonance energy transfer (FRET) principle, a fluorescence dye Cy5-modified survivin siRNA was conjugated to nanogolds (Au-DR-siRNA), which were then wrapped with lipid nanoparticles (LNPs) for monitoring the release behaviour of siRNA in vivo. The results showed that once Au-DR-siRNA was released from the LNPs and cleaved by the Dicer enzyme to produce free siRNA in cells, the fluorescence of Cy5 would change from quenched state to activated state, showing the location and time of siRNA release. Besides, the LNPs showed a significant antitumor effect by silencing the survivin gene and a CT imaging function superior to iohexol by nanogolds. Therefore, this work provided not only an effective method for monitoring the pharmacokinetic behaviour of LNP-based siRNA, but also a siRNA delivery system for treating and diagnosing tumors. [Display omitted]